Water Pipe Leakage Detector Using a Pressure Transmitter Sensor with a Remote Distance Smartphone Display - Perangin-Angin, Bisman (Talenta Publisher, 2021)
This research aimed to design the air pipe leak detection using a pressure transmitter sensor with a smartphone as a display. The research produced a method that can be relied upon by pipe leaks quickly and accurately. The method was carried out by using two flowmeter sensors that are placed before and after the pipe leak point to record data on the difference between intake and exit air flow (Î”Q). The resulting data was transmitted to the computer using a TCP/IP-based network. The results obtained show that the smaller the difference in the flow of air into and out (Î”Q), the farther the pipe leak is (X).